Rental Prices for Housing Units in Norway - Rolf Golombek; Simen Markussen; Tao Zhang (Tidsskrift for boligforskning)
While information on rental prices is critical from a policy perspective, there is limited knowledge on rental prices in Norway. To fill this gap, we estimate a hedonic model for rental prices in Norway, drawing on three data sources. Our framework provides predicted rental prices for housing units in all Norwegian municipalities, whereas the national survey is primarily limited to rental prices in six major Norwegian cities. We find that the rental price is clearly dependent on the number of bedrooms. Moreover, the rent differs by type of housing: terraced housing has the highest rent (everything else being equal), followed by semi-detached housing, apartment and finally detached housing. We also identify that proximity to service centers has a sizable impact on rental prices. Finally, location matters: the rental price in major cities may be more than twice as high as in small towns and rural areas (for housing units with identical attributes).